2020
DOI: 10.3390/antiox9040295
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Alleviates Airway Hyperresponsiveness and Oxidative Stress in Asthmatic Mice

Abstract: Sesamol, isolated from sesame seeds (Sesamum indicum), was previously shown to have antioxidative, anti-inflammatory, and anti-tumor effects. Sesamol also inhibited lipopolysaccharide (LPS)-induced pulmonary inflammatory response in rats. However, it remains unclear how sesamol regulates airway inflammation and oxidative stress in asthmatic mice. This study aimed to investigate the efficacy of sesamol on oxidative stress and airway inflammation in asthmatic mice and tracheal epithelial cells. BALB/c mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…Natural antioxidant compounds are important in modulating diseases associated with environmental pollutants causing oxidative stress by scavenging free radicals (Majdalawieh & Mansour, 2019). In a study, sesamol alleviates airway hyperresponsiveness and oxidative stress in asthmatic mice (Liou et al., 2020). Ren et al.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antioxidant compounds are important in modulating diseases associated with environmental pollutants causing oxidative stress by scavenging free radicals (Majdalawieh & Mansour, 2019). In a study, sesamol alleviates airway hyperresponsiveness and oxidative stress in asthmatic mice (Liou et al., 2020). Ren et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported the biomedical applications of herbal medicines [ 346 , 347 , 348 , 349 , 350 , 351 , 352 , 353 , 354 , 355 , 356 , 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 ]. Antibiotics and other chemical antimicrobial agents including metal oxide and metal nanoparticles can inhibit bacteria growth but also lead to ROS generation and other side effects.…”
Section: Conclusion and The Future Outlookmentioning
confidence: 99%
“…A study reported that it decreased the eosinophil infiltration in lungs, Th2 cytokines, and MDA levels in asthmatic BALB/c mice, and BEAS-2B cells. Further, it reduced the levels of eotaxin, ROS, and ICAM-1 (suppressing adherence of monocytic cell), which might attenuate inflammations in the lungs [ 324 ].…”
Section: Anti-inflammatory Role Of Spicesmentioning
confidence: 99%